An Essay on Making Globalization Fair: The ILO Way - Mohd Ossama (International Journal of Engineering and Management Research, 2020)
Globalization is a process of interconnectedness and liberalization in trade and commerce in the world; flow of information, technology and resources also happens with it. It has its impact, on positives and on some negatives. Growing calls for a fair globalization talks of more inclusion, rights and equality. This essay highlights the role of International Labour Organization (ILO) and its various declarations, especially Declaration on Social Justice for a Fair Globalization for a fairer and sustainable globalization, where demands of each section is met and for a shared prosperous future.